2011
DOI: 10.1128/mmbr.00022-11
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Hydrolases of Escherichia coli

Abstract: SUMMARY The review summarizes the abundant information on the 35 identified peptidoglycan (PG) hydrolases of Escherichia coli classified into 12 distinct families, including mainly glycosidases, peptidases, and amidases. An attempt is also made to critically assess their functions in PG maturation, turnover, elongation, septation, and recycling as well as in cell autolysis. There is at least one hydrolytic activity for each bond linking PG components, and most hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
239
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(240 citation statements)
references
References 323 publications
(572 reference statements)
1
239
0
Order By: Relevance
“…It was proposed in the 'three-for-one' model that PG turnover is a result of a PG remodeling mechanism that replaces one existing strand with three new strands (12). E. coli has many glycosidases, but puzzlingly, none of them have been shown to be essential (2,45). Our simulations suggest a different explanation for how PG is released: glycosidases cleave loose uncrosslinked PG tails.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It was proposed in the 'three-for-one' model that PG turnover is a result of a PG remodeling mechanism that replaces one existing strand with three new strands (12). E. coli has many glycosidases, but puzzlingly, none of them have been shown to be essential (2,45). Our simulations suggest a different explanation for how PG is released: glycosidases cleave loose uncrosslinked PG tails.…”
Section: Discussionmentioning
confidence: 58%
“…The second strategy would involve glycosidases that target PG tails but not crosslinked PG. E. coli does, in fact, have multiple glycosidases, but how they are regulated is not known (2,45). If they were free to cleave any glycosidic bond, presumably the cell would lyse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, flagellar assembly would require the activity of an endo-acting lytic to create these pores along the PG sacculus at varying positions distinct from regions of continuing growth or division where other autolysins (e.g. LTs) function (11)(12)(13)15). This study introduces the first characterized ␤-N-acetylglucosaminidase found in Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In many bacteria, including E. coli, the glycan backbone of PG is degraded by LTs that cleave the β-1,4 glycosidic bond via a mechanism that creates a 1,6-anhydroMurNAc end (7,24,25). Thus, denuded glycans generated by cell-wall amidases are expected to persist longer and accumulate to higher than normal levels in an LT mutant.…”
Section: Spor Domains Bind Septal Regions Of Purifiedmentioning
confidence: 99%